2017
DOI: 10.3390/ijms18020350
|View full text |Cite|
|
Sign up to set email alerts
|

AKT Axis, miR-21, and RECK Play Pivotal Roles in Dihydroartemisinin Killing Malignant Glioma Cells

Abstract: Dihydroartemisinin (DHA), a semi-synthetic derivative of artemisinin, is known to play important roles in inhibiting proliferation rate, inducing apoptosis, as well as hindering the metastasis and invasion of glioma cells, but the underlying mechanisms are still unclear so far. In this study, methyl thiazolyl tetrazolium (MTT), colony-forming, wound healing, invasion, and apoptosis assays were performed to investigate the effect of DHA on malignant glioma cells. Results showed that DHA induced apoptosis of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Consistent with our study, a study has reported that the expression of miR-21 was significantly raised in blood of patients affected by glioma [29]. Another study has presented that miR-21 expression was dramatically elevated in malignant glioma cells relative to that in the normal human glial cells [30]. A previous study has revealed that the expression of PEG3 was remarkably decreased in glioma cell lines [21].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our study, a study has reported that the expression of miR-21 was significantly raised in blood of patients affected by glioma [29]. Another study has presented that miR-21 expression was dramatically elevated in malignant glioma cells relative to that in the normal human glial cells [30]. A previous study has revealed that the expression of PEG3 was remarkably decreased in glioma cell lines [21].…”
Section: Discussionsupporting
confidence: 91%
“…Elevated miR-21 expression leads to increased glioma cell proliferation, invasion and also chemo-resistance, which indicates poor prognosis and tumor recurrence of glioma patients [ 7 10 ]. On the other hand, downregulation of miR-21 leads to repression of antiapoptotic capacity, reduction of migratory, and invasion, as well as increase of chemical-induced death in glioma cells [ 8 , 11 13 ]. All of these make miR-21 not only a potential glioma marker for diagnosis and prognosis but a target for novel therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…We further investigated the potential downstream pathways that might be responsible for the repressive effect of anti-miR-21 + sh-CXCR4 on tumor progression. In this study, we focused on two pathways 1) PI3K/AKT and 2) Raf/ MEK/ ERK, which both played a vital role in glioma cell fate, and were aberrant in the miR-21 and/or CXCR4 overexpression environment (Ching and Hansel 2010, Guo et al, 2013, Dongfeng et al, 2014, Du et al, 2015, Han et al, 2016, Shao et al 2017). The results from western blot analysis presented no statistically difference in AKT, ERK1/2 among different treatment groups both in glioma cells and xenografts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence shows that miR-21 is overexpressed in gliomas and glioma cells compared to normal tissues, and its expression level is positively correlated with glioma grade (Tao et al, 2013, Lei et al, 2014). Elevated miR-21 expression leads to increased glioma cell proliferation invasion, and also chemo-resistance, which indicates poor prognosis and tumor recurrence of glioma patients (Gabriely et al, 2008, Kwak et al, 2011, Melnik 2015, Hermansen et al, 2016), On the other hand, downregulation of miR-21 leads to repression of anti-apoptotic capacity, reduction of migratory and invasion, as well as increase of chemical-induced death in glioma cells (Gabriely et al 2008, Loges et al, 2012, Luo et al, 2017, Shao et al, 2017). All of these make miR-21 not only a potential glioma marker for diagnosis and prognosis, but a target for novel therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation